Feature extraction and gait classification in hip replacement patients on the basis of kinematic waveform data - Dindorf Carlo; Teufl Wolfgang; Taetz Bertram; Becker Stephan; Bleser Gabriele; Fröhlich Michael (Sciendo, 2021)
Study aim: To find out, without relying on gait-specific assumptions or prior knowledge, which parameters are most important for the description of asymmetrical gait in patients after total hip arthroplasty (THA).